Nuclear lifetime measurements around Z=50 - Efstathiou, Margarita; Vasileiou, Polytimos; Mertzimekis, Theodoros; Zyriliou, Aikaterini; Karadimas, Angelos; Chalil, Achment; Koseoglou, Pavlos; Mărginean, Nicolae; Mihai, Constantin; Costache, Cristian; Lică, Razvan; Mihai, Radu; et al. (HNPS Advances in Nuclear Physics, 2024)
In the present work, a dedicated experimental study of the lifetimes of in Te and Sb isotopes was undertaken at the 9 MV Tandem accelerator at the IFIN-HH. Beams of 11B at 35 MeV impinged on a natAg target to populate the nuclei of interest and study their decay using the activation method. The emitted gamma rays and charged particles were detected by the ROSPHERE and SORCERER arrays. Lifetimes of the decaying isomeric and ground states in 117Te and 115,117Sb were measured. The present results update existing literature data from half a century ago employing a new reaction mechanism to populate the states of interest along with a more advanced array of detectors